Isolated ST-Elevation Myocardial Infarction Involving Leads I and aVL: Angiographic and Electrocardiographic Correlations from a Tertiary Care Center - Abhishek Singh; Sudhanshu Dwivedi; Akshyaya Pradhan; Varun S Narain; Rishi Sethi; Sharad Chandra; Pravesh Vishwakarma; Gaurav Chaudhary; Monika Bhandari; Akhil Sharma (Cardiology Research and Practice)
Background. Determining the infarct-related artery in STEMI during a coronary angiogram can be challenging due to the affliction of multiple vessels. Isolated STEMI involving only EKG leads I and aVL is infrequent. Localization of infarct-related artery based on EKG findings has not been previously done in this subset. Methods. All consecutive de novo acute coronary syndrome (ACS) patients admitted to coronary care unit with ST elevations involving only leads I and aVL were screened for enrollment. Patients with ST elevation in any additional lead and those who refused a coronary angiogram were excluded. Subsequently, a coronary angiogram was done as part of primary PCI or a pharmacoinvasive approach to identify the infract-related artery (IRA). IRA was defined by characteristics of lesion, flow of blood through stenosis, and presence of intracoronary thrombus. Coronary angiogram was interpreted by two independent observers blinded to the EKG findings. ST changes in inferior and precordial leads were analyzed to find ECG predictors of the culprit artery. Results. A total of 54 eligible patients of ACS were included in the study. The first major diagonal (D1) was the most frequent IRA in 35.2% followed by left circumflex-obtuse marginal (LCX-OM11) in 29.6%, left anterior descending (LAD) in 20.4%, and ramus intermedius (RI) in 14.8%. Out of total patients with ST depression in lead V2, the LCX-OM11 group was IRA in 50% cases while the RI, D1, and LAD groups accounted for 31.8%, 13.6%, and 4.5%, respectively (p<0.001). Similarly, LCX-OM1 was the most frequent IRA subjects with ST depressions in leads V1 and V3 (44.4%; p=0.010 and 46.2%; p=0.003, resp.). On the contrary, in patients with ST depression in lead III, LAD and D1 were the most frequent IRA as compared to LCX-OM1 and RI though statistical significance was not attained (p=0.857 for lead III). ST-segment depression in lead V2 had a positive predictive value of 60% and a negative predictive value of 100% for LCX-OM1 as IRA. Similarly, ST-segment depression in lead V2 had a positive predictive value of 20% and a negative predictive value of 100% for the RI group. Conclusions. In patients presenting with isolated ST elevation in leads I and aVL, the most frequent IRA on angiogram was first diagonal. ST depressions in EKG leads V1–V3 were the most common predictor of LCX–OM1 while those in inferior leads indicated LAD-D1 as the IRA.